2012
DOI: 10.1186/1471-244x-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of serum IL-5 are associated with an increased likelihood of major depressive disorder

Abstract: BackgroundInflammatory mediators in both the peripheral circulation and central nervous system (CNS) are dysregulated in major depressive disorder (MDD). Nevertheless, relatively little is known about the role of the T-helper (Th)-2 effector cytokines interleukin (IL)-5 and IL-13 in MDD.MethodsWe examined the serum levels of these cytokines and a Th-1 comparison cytokine, interferon (IFN)-γ, in 116 individuals (MDD, n = 58; controls, n = 58).ResultsIn our basic multivariate model controlling for the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…A recent investigation found that elevated serum levels of IL-5 are associated with an increased risk of major depressive disorder (Elomaa et al, 2012). Another study which assayed the levels of individual analytes found higher levels of eotaxin and lower levels of both MCP-1 and the RANTES protein (regulated-on-activation normal T cell expressed and secreted) in depressed females who had reported suicidal ideations, compared to matched control patients who had no thoughts of suicide (Grassi-Oliveira et al, 2012).…”
Section: Immune Response and Inflammationmentioning
confidence: 98%
“…A recent investigation found that elevated serum levels of IL-5 are associated with an increased risk of major depressive disorder (Elomaa et al, 2012). Another study which assayed the levels of individual analytes found higher levels of eotaxin and lower levels of both MCP-1 and the RANTES protein (regulated-on-activation normal T cell expressed and secreted) in depressed females who had reported suicidal ideations, compared to matched control patients who had no thoughts of suicide (Grassi-Oliveira et al, 2012).…”
Section: Immune Response and Inflammationmentioning
confidence: 98%
“…In consequence, a patient might demonstrate significant clinical changes in the behavior and mood, starting with fits of panic and finishing with suicidal thoughts [32]. According to the monocyte-T-lymphocyte hypothesis the immune system plays a key role in determining someone's personality and temperament, through synthesis, release and uptake of monoamines in the central nervous system [25,33,34]. Decreased or increased expression of synaptic plasticity, neurogenesis, and neuromodulation through basal ganglia, the frontal cortex and activity of the hypothalamus-pituitary axis (HPA) affect the limbic system and influence its various activations [26,27,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that inflammatory mediators are important risk factors of mood disorders and in the course of somatic inflammatory diseases intensified mood disorders correlate with concentration of many inflammatory markers: C-reactive protein (CRP), IL-1, IL-2, IL-5, IL-6, IL-12, IL-13, TNF-α, and Interferon-α [23,24,25,26,27,28,29,30,31]. It was reported that chronic inflammation, which can be observed in asthma, through inflammatory mediators (cytokines) contributes to secondary downregulation of Cyclic adenosine monophosphate Response Element-Binding protein (CREB), Tyrosine Receptor Kinase (TRK) protein and release of Brain-Derived Neurotrophic Factor (BDNF) in frontal lobes and the limbic system, which results in damage to the hippocampus and a decrease in the level of monoamines in the brain [23,24,25]. Also some drugs, such as theophylline, used in asthma therapy correlate with an increase in the level of cyclic Adenosine MonoPhosphate (cAMP) but do not correlate with an increase in the activity of CREB protein, which might result in excitation of the limbic system and an increased catecholamine release.…”
Section: Introductionmentioning
confidence: 99%
“…71 In line with this, elevated levels of serum IL-5 have been associated with an increased likelihood to develop MDD. 72 This study is the first to describe a robust decrease of FGF-2 in PCP-treated rats. FGF-2 has been implicated in the pathophysiology of schizophrenia and the mechanism of action of antipsychotic treatment response.…”
Section: Discussionmentioning
confidence: 75%